R-loop Mediated DNA Damage and Impaired DNA Repair in Spinal Muscular Atrophy - Cuartas, Juliana; Gangwani, Laxman (Frontiers in Cellular Neuroscience, 2022)
Defects in DNA repair pathways are a major cause of DNA damage accumulation leading to genomic instability and neurodegeneration. Efficient DNA damage repair is critical to maintain genomicstability and support cell function and viability. DNA damage results in the activation of cell death pathways, causing neuronal death in an expanding spectrum of neurological disorders, such as amyotrophic lateral sclerosis (ALS), Parkinson’s disease (PD), Alzheimer’s disease (AD), and spinal muscular atrophy (SMA). SMA is a neurodegenerative disorder caused by mutations in the Survival Motor Neuron 1 (SMN1) gene. SMA is characterized by the degeneration of spinal cord motor neurons due to low levels of the SMN protein. The molecular mechanism of selective motor neuron degeneration in SMA was unclear for about 20 years. However, several studies have identified biochemical and molecular mechanisms that may contribute to the predominant degeneration of motor neurons in SMA, including the RhoA/ROCK, the c-Jun NH2-terminal kinase (JNK), and p53-mediated pathways, which are involved in mediating DNA damage-dependent cell death. Recent studies provided insight into selective degeneration of motor neurons, which might be caused by accumulation of R-loop-mediated DNA damage and impaired non-homologous end joining (NHEJ) DNA repair pathway leading to genomic instability. Here, we review the latest findings involving R-loop-mediated DNA damage and defects in neuron-specific DNA repair mechanisms in SMA and discuss these findings in the context of other neurodegenerative disorders linked to DNA damage.